Laser-induced gas-phase transfer and direct stamping of nanomaterials: comparison of nanosecond and femtosecond pulses - N T Goodfriend; I Mirza; A V Bulgakov; E E B Campbell; N M Bulgakova (Materials Research Express)
The two-dimensional nanomaterial, hexagonal boron nitride (hBN) was cleanly transferred via a blister-based laser-induced forward-transfer method. The transfer was performed utilizing femtosecond and nanosecond laser pulses for separation distances of ∼16 and ∼200 μm between a titanium donor film deposited on a glass substrate and a silicon/silicon dioxide receiver. The transfer efficiency was examined for isolated laser pulses as well as for a series of overlapping pulses for both pulse durations. The damage-free transfer of monolayer and multilayer hBN was demonstrated for all tested combinations of pulse duration and transfer distances. The results indicate that transfer proceeds via direct stamping for short donor-to-receiver distances while, for the larger distance, the material is ejected from the donor and lands on the receiver. Furthermore, with overlapping pulses, ns laser pulses enable a successful printing of hBN lines while, for fs laser pulses, the Ti film can be locally disrupted by multiple pulses and molten titanium may be transferred along with the hBN flakes. For reproducibility, and to avoid contamination with metal deposits, low laser fluence transfer with ns pulses and transfer distances smaller than the blister height provide the most favourable and reproducible condition.